Pendidikan Kesehatan Keluarga Berencana Pada Wanita Usia Subur Di Dukuh Kuncen, Desa Cawas, Klaten - Endang Sawitri; Nur Wulan Agustina; Endang Wahyuningsih; Supardi; Tetrine Prameswari (WASATHON Jurnal Pengabdian Masyarakat, 2024)
Family planning is an attempt to span or plan the number and spacing of pregnancies using contraception. Family planning is a program that helps individuals or married couples to avoid unwanted births, regulate the interval between pregnancies, control the time and birth in conjugal relationships and determine the number of children in the family. The number of family couples who do not know about various types of contraceptives, providing health education can increase knowledge about family planning acceptors, thus making family planning acceptors more precise in determining contraceptives that are comfortable to use and can avoid errors in the selection of tools. Methodology. Health education was held on Thursday, June 13, 2024 at the Nur Islam Mosque RT 001 / RW 009 at 16.00 WIB. The implementation was carried out with 2 stages: The first stage of the service implementer begins the activity by meeting directly with Kuncen village cadres to identify existing problems and conduct introductions and socialization related to community service activities to provide counseling on family planning (KB) then provide online invitations to participants. The second stage is the distribution of leaflets to the participants who attended the health education results: The results showed that the RW 009 community in Kuncen Hamlet, Cawas Village were enthusiastic in receiving education and the participants were active in the question and answer session. Community knowledge increased after being given education, the community was able to answer questions properly and correctly Conclusion: The results after conducting health education about family planning can be seen that the knowledge of women of childbearing age has increased.